2014
DOI: 10.1097/mib.0000000000000183
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation-associated Adherent-invasive Escherichia coli Are Enriched in Pathways for Use of Propanediol and Iron and M-cell Translocation

Abstract: Our findings provide novel insights into the genetic basis of the AIEC pathotype, supporting the concept that AIEC are equipped to exploit and promote intestinal inflammation and reveal potential targets for intervention against AIEC and inflammation-associated dysbiosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
185
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 142 publications
(203 citation statements)
references
References 79 publications
8
185
3
Order By: Relevance
“…When we analyzed the presence of gipA gene in E. coli strains according to their adherent and invasive phenotype, we observed that percentages of gipA-positive AIEC strains were higher (31.4%) than gipA-positive non-AIEC strains (19.4%) ( Table 1). Importantly, 100% of the gipA-positive AIEC strains also harbored the lpf operon encoding LPF previously reported to be involved in the targeting of PPs by AIEC strains, 16,17 whereas none of the gipA-positive non-AIEC strains was positive for lpfA. Among the sequenced pathogenic and nonpathogenic E. coli strains that were positive for gipA (see Table S3, Supplemental Digital Content 3, http://links.lww.com/IBD/B129), none of them harbors the lpf operon.…”
Section: Prevalence Of Gipa-positive E Coli Strains In CD Patients Amentioning
confidence: 99%
See 1 more Smart Citation
“…When we analyzed the presence of gipA gene in E. coli strains according to their adherent and invasive phenotype, we observed that percentages of gipA-positive AIEC strains were higher (31.4%) than gipA-positive non-AIEC strains (19.4%) ( Table 1). Importantly, 100% of the gipA-positive AIEC strains also harbored the lpf operon encoding LPF previously reported to be involved in the targeting of PPs by AIEC strains, 16,17 whereas none of the gipA-positive non-AIEC strains was positive for lpfA. Among the sequenced pathogenic and nonpathogenic E. coli strains that were positive for gipA (see Table S3, Supplemental Digital Content 3, http://links.lww.com/IBD/B129), none of them harbors the lpf operon.…”
Section: Prevalence Of Gipa-positive E Coli Strains In CD Patients Amentioning
confidence: 99%
“…16,17,50 Type 1 pilus expression is regulated by a process called phase variation, in which the bacteria switch between piliated and nonpiliated states under the control of a switch invertible element, located upstream of the type 1 pilus-encoding operon. PCR experiments using 2 sets of primers specific to ON and OFF orientations of the invertible element demonstrated that type 1 pilus expression was not impaired as a consequence of gipA deletion (Fig.…”
Section: Gipa Regulates Long Polar Fimbriae Expressionmentioning
confidence: 99%
“…A functionally distinct group of resident enteric E. coli bacteria known as adherent-invasive E. coli (AIEC) are recovered more frequently and in larger quantities from ileal tissue biopsy specimens from CD patients than from specimens from non-CD controls (7,8). In the absence of common identifying genetic determinants (9), AIEC strains are characterized by their ability to adhere to and invade intestinal epithelial cells (10) and to survive and replicate within macrophages (11). AIEC strains are also moderate to strong in vitro biofilm producers (12).…”
mentioning
confidence: 99%
“…Consequently, little is known about the impact of iron on the functional attributes of AIEC strains. Therefore, the goal of this study was to characterize how iron impacts the physiology of the AIEC strain NC101 (9,44) and subsequent interactions with macrophages. Here we show that iron promotes the cellulose-dependent aggregation of NC101.…”
mentioning
confidence: 99%
“…Additionally, recent work reported a prevalence of approximately 25% for AIEC in patients with ileal CD. 20 AIEC strains have the ability to adhere to and invade epithelial cells and produce extensive biofilms that protect bacteria from the host immune system and antibiotic therapy. 19,21,22 For the ileal isolates, this opportunism is linked to abnormally increased expression of CEACAM6 receptors in patients with CD in which AIEC bacteria are able to adhere through FimH of the bacterial type I pilus.…”
mentioning
confidence: 99%